1975
DOI: 10.1128/aac.8.5.538
|View full text |Cite
|
Sign up to set email alerts
|

Human Therapeutic and Agricultural Uses of Antibacterial Drugs and Resistance of the Enteric Flora of Humans

Abstract: Fecal samples were collected from five groups of people differing in the manner of their exposure to antibacterial drugs. The groups included: (i) people working on farms who were continuously in contact with the predominantly resistant florae of farm animals receiving rations containing antibacterial drugs, (ii) people residing on the same farms with no direct exposure to the farm animals, (iii) people treated with antibacterial drugs, (iv) untreated people residing with treated individuals, and (v) untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Transmission of E. coli from poultry to man 521 intestinal tract of poultry (5,8,12,14,27,30). Where the resistance factor contains genes for resistance to more than one antibiotic, the use of a single agent will select for multiple resistance (31) and this may complicate the therapy of veterinary as well as human infections.…”
Section: D)isctusstonmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission of E. coli from poultry to man 521 intestinal tract of poultry (5,8,12,14,27,30). Where the resistance factor contains genes for resistance to more than one antibiotic, the use of a single agent will select for multiple resistance (31) and this may complicate the therapy of veterinary as well as human infections.…”
Section: D)isctusstonmentioning
confidence: 99%
“…Such non-therapeutic uses have been of major concern to those engaged in the treatment of infectious diseases, especially as a correlation has been found between the widespread use of antimicrobial drugs and the emergence of drug resistance (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Thus, resistance patterns of animal E. coli isolates have been found to be similar to those found among the isolates from humans who were closely associated with the animals (7,14,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this was due to the relatively short period of time the human subjects were in contact with tetracycline and/ or the calves, or the highly restrictive measures taken by the human subjects to preclude transfer of microorganisms out of the isolation unit (e.g., changing clothes), is not known. Epidemiologic studies have shown that contact with animals on antimicrobials is reflected to a high degree in the resistance of the enteric flora (Linton et al, 1972;Wells and James, 1973;Siegel et al, 1975). Human subjects in these studies had long term contact with the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts have been made to draw a relationship between the R factor gene pool in animals, antimicrobic pressures exerted on the pool, and the occurrence of resistance genes in the enteric microorganisms in the enteric tract of man. Most of the investigations have been indirect and epidemiological in scope (Linton et al, 1972;Wells and James, 1973;Fein et al, 1974;Dorn et al, 1975;Siegel et al, 1975). All these studies have shown that a direct correlation exists between animal contact, antimicrobic usage, and the occurrence of multiply-resistant flora in the enteric tracts of the human contacts.…”
Section: Introductionmentioning
confidence: 99%
“…We describe the results of a study that was designed to: (1) show the magnitude of antibiotic resistance in selected bacteria isolated from patients admitted to a hospital in the Asir region of Saudi Arabia; (2) screen these strains for plas-mid-borne antibiotic resistance; and (3) test the feasibility of using the plasmid profile analysis to show strain relationships and demonstrate the potential of the technique in tracing cross infections.…”
mentioning
confidence: 99%